World Development Report, 1980 - World Bank, Washington, DC. (Washington : World Bank, 1980)
The report, third in a series of annual publications, examines some of the difficulties and prospects in areas of social and economic progress and human development which developing countries face during the next decade. Distinguishing oil-importing from oil-exporting developing countries, the first part of the report presents global and regional projections and discusses international policy issues in energy, trade, and capital flows. The second part focuses on human development: education and training, health, nutrition, and fertility reduction. The report provides a brief discussion of human development problems and priorities in each of the major regions of the developing world. It gives particular attention, however, to the two regions in which absolute poverty is most serious: Sub-Saharan Africa, which combines the worst growth prospects with the lowest levels of literacy and life expectancy; and South Asia, which contains half of the world's poor. Human development is shown to be important not only in alleviating poverty directly, but also in increasing the incomes of the poor, and Gross National Product growth as well. The vital message is that some steps known to be morally right--primary education, for example--make good economic sense as well. (Author)
Microfiche.
Keywords: Adult Education; Birth Rate